Measuring Malnutrition and Intestinal Helminthiasis on Tobacco Plantation Workers’ Children - Chairuddin P. Lubis; Helena Siregar; Alogo Siregar; Ratna Maulana Lubis (Indonesian Pediatric Society, 1979)
Assessment of nutritional status and fecal examination for intestinal helminthiasis were conducted on 317 children of Tobacco Plantation workers. The nutritional status was measured by using the